Case series of buprenorphine injectors in Kuala Lumpur, Malaysia - Bruce, R.D.; Govindasamy, S.; Sylla, L.; Haddad, M.S.; Kamarulzaman, A.; Altice, F.L. (2008)
Diversion of buprenorphine has been described in settings where it is legally prescribed and has become an increasing concern in Malaysia; it resulted in banning of buprenorphine in Singapore where unsubstantiated case reports suggested that buprenorphine injection was associated with particularly poor outcomes. We therefore conducted a case series of qualitative interviews with buprenorphine injectors in Kuala Lumpur, Malaysia to examine further the issues surrounding buprenorphine injection as well as the abuse of midazolam in combination with buprenorphine. Interviews with 19 men do not suggest significant adverse health consequences from buprenorphine injection alone and injectors have adapted diverted buprenorphine as a treatment modality. A subset of these injectors, however, combined buprenorphine and midazolam for euphoric effects with resultant symptoms of a possible pharmacological interaction. Prospective cohort studies, rather than hospital-derived samples, are needed to better understand the safety of buprenorphine injection.